Epidemiology of Emergencies in a Hospital in Sub-Saharan Africa - D., Barboza; MA, Manga; I., Gaye; EN, Diop; EB, Ba; M., Diédhiou (International Journal of Innovative Research in Medical Science, 2020)
Objective: Assess the epidemiology of emergencies received in the emergency care unit of “Peace Hospital” of Ziguinchor. Material and methods: It was a prospective, descriptive and analytic study in the emergency care unit of “Peace Hospital” during the period from the April 01, 2017 to May 31, 2017. Results: During the study period, 762 patients were collected. The mean age of patients was 35.1 years with extremes of 1 month and 91 years. The patients were mostly in the 20-39 years old range. The female sex was predominant at 55.6%. Most of our patients came from the Ziguinchor department with a proportion of 82.3%. The majority of patients or 92.7% arrived at the emergency care unit by taxi or private vehicle. Among the patients transferred by ambulance, 41.5% had been subject to effective regulation. The majority of patients (45.3%), had a length of stay of less than one hour. The predominant pathologies were digestive pathologies in 20.3%, followed by respiratory pathologies in 14.8%. The return home was effective in 80.7% of patients. The overall mortality rate was 5.6%. The factors of severity were the age ≥ 60 years, serious pathologies, non-medicalization of ambulances, late referral, the long-term length of hospitalization in the emergency care unit. Conclusion: Emergency care units often face difficulties with human resources and material.